Impact of Electronic Hand Hygiene Monitoring on Hospital-Acquired Clostridium difficile Infection Rates. (4th October 2017) - Knepper, Bryan; Miller, Amber; Ruff, Kevin; Van Winks, Tina; Zoetewey, Julie; Douglas, Ivor; Hanley, Michael; Young, Heather
Abstract: Background: Lower rates of hand hygiene adherence are linked to increased risk of nosocomial transmission of infectious pathogens, thereby increasing morbidity and mortality. Assessing true adherence is difficult using direct observation due to the low number of observations collected, heterogeneous observer training and bias, and the Hawthorne effect. We assessed whether radio frequency identification (RFID) hand hygiene monitoring resulted in changes to our hospital-onset Clostridium difficile (HO-CDI) rates. We also assessed whether electronically measured hand hygiene improved by the end of the intervention period. Methods: The RFID system was installed in Apr 2016 in 2 medical/surgical units, a progressive care unit, and an intensive-care unit (study group). Registered nurses, certified nursing assistants, and selected physicians wore RFID badges to track hand hygiene adherence. Adherence is defined as washing with soap or alcohol-based hand rub within 1 minute before or after entering or exiting a patient's room. A second set of rooms (1 ICU, 1 short-stay unit, and 5 medical/surgical units) without the system served as the control group. HO-CDI rates were tracked monthly for each group using NHSN definitions. HO-CDI trends were compared for 15 months before and 12 months after installation of the system using interrupted time series analysis. Average electronic hand hygiene adherence for the first two months and last two months of the intervention period was compared using the Wilcoxon rank-sum test. Other interventions aimed at reducing HO-CDI were consistently applied to both the study and control groups. Results: One hundred and eighty-six HO-CDI occurred: 73 in the study group and 113 in the control group. In the study group, the trend in HO-CDI rates changed from increasing in the pre-intervention to decreasing in the post-intervention (P = 0.02) (Figure 1). HO-CDI rates in the control group demonstrated no change in trend (P = 0.69) (Figure 2). In the study group, electronically tracked hand hygiene adherence increased from a mean of 46% in Apr-May 2016, to 77% in Feb-Mar 2017 (P < 0.0001). Conclusion: Electronic RFID hand hygiene systems can have a tangible effect on hospital-acquired infection rates. This result strengthens the argument for using these systems to improve patient safety. Disclosures: All authors: No reported disclosures.